Long-Term Consequences of Radiation-Induced Bystander Effects Depend on Radiation Quality and Dose and Correlate with Oxidative Stress - Buonanno, Manuela (2011)
Widespread evidence indicates that exposure of cell populations to ionizing radiation results in significant biological changes in both the irradiated and nonirradiated bystander cells in the population. We investigated the role of radiation quality, or linear energy transfer (LET), and radiation dose in the propagation of stressful effects in the progeny of bystander cells. Confluent normal human cell cultures were exposed to low or high doses of 1GeV/u iron ions (LET ~ 151 keV/μm), 600 MeV/u silicon ions (LET ~ 51 keV/μm), or 1 GeV protons (LET ~ 0.2 keV/μm). Within minutes after irradiation, the cells were trypsinized and co-cultured with nonirradiated cells for 5 h. During this time, irradiated and nonirradiated cells were grown on either side of an insert with 3-μm pores. Nonirradiated cells were then harvested and allowed to grow for 20 generations. Relative to controls, the progeny of bystander cells that were co-cultured with cells irradiated with iron or silicon ions, but not protons, exhibited reduced cloning efficiency and harbored higher levels of chromosomal damage, protein oxidation and lipid peroxidation. This correlated with decreased activity of antioxidant enzymes, inactivation of the redox-sensitive metabolic enzyme aconitase, and altered translation of proteins encoded by mitochondrial DNA. Together, the results demonstrate that the long-term consequences of the induced nontargeted effects greatly depend on the quality and dose of the radiation and involve persistent oxidative stress due to induced perturbations in oxidative metabolism. They are relevant to estimates of health risks from exposures to space radiation and the emergence of second malignancies after radiotherapy.